Academic writing : intercultural and textual issues - Ventola, Eija; Mauranen, Anna (Pragmatics & beyond ;, 1996)
Writing is crucial to the academic world. It is the main mode of communication among scientists and scholars and also a means for students for obtaining their degrees. The papers in this volume highlight the intercultural, generic and textual complexities of academic writing. Comparisons are made between various traditions of academic writing in different cultures and contexts and the studies combine linguistic analyses with analyses of the social settings in which academic writing takes place and is acquired. The common denominator for the papers is writing in English and attention is given t.